A territorialised UN Agenda 2030 in Portugal: Cross-cutting issues in energy, environment and health - Medeiros, E. (6ª Edição do Workshop Interno do DINÂMIA'CET_Iscte: Dinâmicas Socioeconómicas e Territoriais Contemporâneas | 2022. Livro de Resumos, 2022)
It goes without saying that the world is far off course for achieving a desirable sustainable development path. Crucially, this policy goal has been on the global agenda for more than four decades. In 2015, the United Nations (UN) presented the Agenda 2030 with its 17, now famous, action-oriented sustainable development goals (SDGs), as a powerful thematically holistic policy itinerary. In this context, this chapter builds on the partnership agreement with the European Commission (EC), also known as Portugal 2020 (European Union (EU) Cohesion Policy framework for 2014-2020 in Portugal) and its potential contribution to supporting sustainable policy transitions. This paper presents a theoretical discussion on sustainable policies and practices in energy, environment and health and proposes a conceptual framework to better analyse sustainable policy transitions. Supported by Portugal 2020’s strategy and project analysis, it is possible to conclude that Portugal has been supporting the UN Agenda 2030 vision for a more environmentally sustainable territory, and that there are several cross-cutting projects that have been implemented in the energy, environment and health sectors. However, the Portugal 2020 intervention is mainly focused on financing physical renovation to improve energy efficiency processes.